AB0867 Pegloticase re-treatment after a gap in therapy: data from two phase iii trials and an open-label extension study. (15th June 2017) - Baraf, HS; Morton, A; LaMoreaux, B; Kent, J
Abstract : Background: Pegloticase is a PEGylated recombinant uricase approved in the US for treating adult patients with chronic refractory gout. As a biologic medication, pegloticase is administered intravenously every 2 weeks. It is currently not known whether a gap in the standard biweekly regimen can be tolerated or would be associated with a loss of efficacy. During the pivotal trial testing of pegloticase, some patients experienced a delay between participation in the randomized controlled trial (RCT) and the open-label extension (OLE) that followed. Analysis of the clinical impact of this gap was carried out to understand whether therapeutic benefit would be affected. Objectives: The objective of this analysis was to determine, among pegloticase responders, the effect of a 28 or more day gap between doses of pegloticase on the subsequent urate lowering response and frequency of infusion reactions. Methods: These analyses utilized results from two RCTs of pegloticase and a 2-year OLE. In the RCTs, 36 of 85 patients, who were dosed with pegloticase every two weeks, were classified as responders (persistent urate lowering during intensive monitoring at 3 and 6 months of the RCT), and went on to enroll in the OLE and receive additional doses of pegloticase. Of these 36 patients, 14 had a gap between pegloticase doses of more than 28 days. Results: Among the 14 patients with a gap of more than 28 days between doses of pegloticase therapy the length of the gap ranged from 34 to 167 days (mean =72.5 days, median =59.5 days). Of these 14 patients, 8 received pegloticase on an every-4-week dosing schedule in the OLE and 6 remained on every-2-week dosing. Ten of the 14 patients maintained their serum urate level <6mg/dL in the OLE. Five of 6 that remained on every 2 week dosing and 5 of 8 that went to every 4 week dosing continued to have serum urate <6mg/dL. (see table 1 ). By logistic regression analysis, the length of the gap had no significant effect on the subsequent urate lowering effect of pegloticase. Of the fourteen patients with a gap in pegloticase therapy, 2 (14%) had infusion reactions during a total of 632 infusions in the OLE yielding a re-treatment IR rate of 0.32%. Conclusions: The majority of patients in this limited dataset who were previously responders to pegloticase dosed every 2 weeks continued to maintain a serum urate lowering response to pegloticase after a gap in therapy. Infusion reactions during re-treatment occurred in 2 patients with a re-treatment infusion reaction rate of 0.32%. References: Sundy, J.S., Baraf, H.S.B., Yood, R.A., et al. Efficacy and tolerability of pegloticase for the treatment of chronic gout in patients refractory to conventional treatment, JAMA, 2011;306(7):711–720. Becker, M.A., Baraf, H.S.B., Yood, R.A., et al. Long-term safety of pegloticase in chronic gout refractory to conventional treatment, Ann Rheum Dis, 2013;72:1469–1474. Lipsky, P.E., Calabrese, L.H., Kavanaugh, A., et al. Pegloticase immunogenicity: the relationship between efficacy and antibody development in patients treated for refractory chronic gout, Arthritis Research & Therapy, 2014;16:R60. Disclosure of Interest: H. Baraf Consultant for: Horizon Pharma, Takeda, Ironwood, A. Morton Consultant for: Pfizer, Sanofi Regeneron, Ironwood, Horizon, Speakers bureau: Prizer, Amgen, Abbvie, Janssen, Celgene, Horizon, Novartis, Ironwood, B. LaMoreaux Employee of: Horizon Pharma, J. Kent Employee of: Horizon Pharma